TINDAKAN (BULLYING) DALAM DUNIA PENDIDIKAN DITINJAU DARI PERSFEKTIF HUKUM PIDANA ISLAM - Eko Suseno (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2018)
Bullying in the world of education is a despicable act and is forbidden by Islam because it can hurt victims both physically and mentally. this research was conducted using a normative method where the material used came from the literature and other library sources. Conversely, if abuse is carried out by students or students who are still underage, then the offender is subject to ta'zir punishment in the form of diyath, kaffarah, alternative or substitute punishment ('uqubât al-badilâh) which aims to educate or give lessons to other actors and people do not answer the same deed. The results of this study are that bullying is an illicit act that can cause harm both physically and mentally to the victim. Abuse occurs because the quality of one's faith is so low that the person will tend to act harsh, cruel, destructive and blindly hate.